EFL instructors’ views on the use of phonetic symbols for teaching pronunciation - Durukan, Dilek; Gokgoz-Kurt , Burcu (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2024)
As a bottom-up approach to pronunciation teaching, the use of phonetic symbols in language teaching classrooms has been controversial. Therefore, the present study aimed at investigating the views of Turkish instructors of English as a foreign language regarding their use of phonetic symbols for teaching pronunciation at tertiary-level institutions. To achieve this goal, semi-structured interviews were conducted with six instructors of English as a foreign language from the same institution. The qualitative findings indicate that while almost all instructors value the role of phonetic symbols they express various teacher-related and student-related concerns which lead to avoidance of using phonetic symbols and make recommendations. Participants also maintain that teacher training, technology integration, and student self-monitoring as a means of assessment are crucial for effective pronunciation instruction using phonetic symbols.